2021
DOI: 10.5694/mja2.51009
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes for people with serious mental illness are poorer than for other patients: a systematic review and meta‐analysis

Abstract: atients with serious mental illness who require surgical care are routinely treated in non-psychiatric hospitals. 1 As the prevalence of serious mental illness is relatively low (2-3% in Australia 2 ), it is unsurprising that surgeons only infrequently ask patients about their mental health before operations, and lack confidence in caring for these vulnerable and complex patients. 3 Serious mental illness should be treated like any other medical comorbidity and managed pro-actively, both before and after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
(183 reference statements)
2
17
0
Order By: Relevance
“…To our knowledge, no published study has identified mood disorder as a risk factor for pneumonia after cancer surgery. In general, patients with mental illness are at an increased risk of various postoperative complications, including pneumonia [ 28 ]. Patients with severe mental illness are more likely to have poor insight into their overall health and difficulty in self-care, which can negatively affect hygiene [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no published study has identified mood disorder as a risk factor for pneumonia after cancer surgery. In general, patients with mental illness are at an increased risk of various postoperative complications, including pneumonia [ 28 ]. Patients with severe mental illness are more likely to have poor insight into their overall health and difficulty in self-care, which can negatively affect hygiene [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative mental condition for patients is significantly correlated with physical outcomes and can dramatically influence the quality of life, thus leading to public health concerns ( 1 , 2 ). Individuals with preoperative stress are prone to postoperative emotional deficits, especially adolescent patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depression, common in the postoperative setting, makes it especially challenging to perform healthy behaviors and thus predicts worse weight loss outcomes following bariatric surgery. Broadly speaking, serious mental illness increases the odds of postoperative complications and longer hospital stays [3].…”
mentioning
confidence: 99%